Clinician$1 (Bs Manual on Myelodysplastic Syndromess - List, Alan.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2008)
An overview of diagnosis and current management of myelodysplastic syndromes. - Reviews the performance of the pharmacological treatments currently available and analyses the potential for new treatments - High quality clinical photos and figures to enhance descriptions and improve reader comprehension - Useful reference text for healthcare professionals needing to know more about myelodysplastic syndromes.
to myelodysplastic syndromes -- Etiology and pathophysiology -- Signs and symptoms of myelodysplastic syndromes -- Clinical assessment and diagnosis -- Classification of myelodysplastic syndromes -- Management of myelodysplastic syndromes.
Keywords: Medicine; Hematology; Oncology; Medicine & Public Health; Oncology; Hematology; Electronic books